Financial stability, return, and asset, liability, and income diversification in Mexican largest bank - Llanos Reynoso, Luis Felipe; Vela Beltrán del Río, César (Revista Mexicana de Economía y Finanzas Nueva Época REMEF, 2023)
The current article is an analysis of the Mexican largest banks, aiming to establish if asset, liability, and / or income diversification affects, positively or negatively, and simultaneously both financial stability and return. We used 2010-2021 information and performed several linear and polynomial regression analyzes. Previous research papers considered two predictor, in the best cases. On this sense, the scope of our analysis is broader because we analyzed the Mexican banking systems with three potential predictors. Our research´s results indicate that for profitability purposes, asset and / or income concentration or specialization are optimal strategies. However, to reduce risk, banks should diversify their assets and / or income base. In terms of liabilities, banks might try to find the inflection point where maximizing return and minimizing risk are simultaneously achieved. Our conclusion is that diversification in general does not positively and simultaneously impact both risk and return. In other words: selective asset and income concentration positively impact return and that selective asset and income diversification reduce risk. Liabilities are more difficult to manipulate to achieve the mentioned objectives.